Expression of Alzheimer-Type Neurofibrillary Epitopes in Primary Rat Cortical Neurons Following Infection with Enterococcus faecalis - Underly, Robert; Song, Mee-Sook; Dunbar, Gary L.; Weaver, Charles L. (Frontiers in Aging Neuroscience, 2016)
The neurofibrillary tau pathology and amyloid deposits seen in Alzheimer's disease (AD) also have been seen in bacteria-infected brains. However, few studies have examined the role of these bacteria in the generation of tau pathology. One suggested link between infection and Alzheimer’s disease is edentulism, the complete loss of teeth. Edentulism can result from chronic periodontal disease due to infection by Enterococcus faecalis. The current study assessed the ability to generate early Alzheimer-like neurofibrillary epitopes in primary rat cortical neurons through bacterial infection by Enterococcus faecalis. Seven-day old cultured neurons were infected with Enterococcus faecalis for 24- and 48-hours. An upward molecular weight shift in tau by western blotting and increased appearance of tau reactivity in cell bodies and degenerating neurites was found in the 48-hour infection group for the antibody CP13 (phospho-Serine-202). A substantial increase in reactivity of Alz-50 was seen at 24- and 48- hours after infection. Furthermore, extensive MAP2 reactivity also was seen at 24- and 48-hours post-infection. Our preliminary findings suggest a potential link between Enterococcus faecalis infection and intracellular changes that may help facilitate early AD-like neurofibrillary pathology.